KUALITAS BUTIR-BUTIR SOAL UNTUK RANAH KOGNITIF PADA MEDIA PEMBELAJARAN ARITMETIKA - Rudi Gunawan; Ahmad, Ahmad Afif Supianto; Admaja, Admaja Dwi Herlambang (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The assessment of technology-based learning media is essential for effectively supporting learning activities. A thorough analysis of the quality of the assessment items included in the learning media is vital, as it ensures that each question accurately evaluates the cognitive abilities of students. This study utilizes the results of student answers, items of questions, and the answer keys to practice questions used in the interactive learning media Monsakun for arithmetic learning. This research used a quantitative descriptive method. The objective of this study is to analyze the distribution of cognitive domain aspects, the difficulty level of the questions, and the distinguishing power of the items that have been interpreted according to established criteria. The analysis results indicate that the questions formulated within the interactive learning media of Monsakun are well-structured, effectively integrating questions related to everyday life concepts. However, the proportion of questions in terms of cognitive capabilities implemented is too much to adopt higher Order Thinking Skills (HOTS) type questions without considering the proportion aspect of balance. Therefore, it is necessary to rearrange the items in the interactive learning media Monsakun to be able to measure the extent of learning outcomes.